Based on bioinformatics analysis lncrna SNHG5 modulates the function of vascular smooth muscle cells through mir‐205‐5p/SMAD4 in abdominal aortic aneurysm - Han Nie; Wenpeng Zhao; Shizhi Wang; Weimin Zhou (Immunity, Inflammation and Disease, 2021)
Abstract Objective The aim of this study was to explore expression profiles of long noncoding RNA (lncRNA)‐messenger RNA (mRNA) in abdominal aortic aneurysm (AAA) patients. Further, we explored the mechanisms by which lncRNA SNHG5 modulates the function of vascular smooth muscle cells (VSMC) in AAA. Methods Human gene expression profile GSE57691 dataset, was retrieved from Gene Expression Omnibus database. The dataset included gene expression array data of 49 AAA patients and 10 control aortic specimens from organ donors. To explore the main roles of the biological network, differentially expressed lncRNA and mRNAs in the aortic aneurysm (AAA) and normal aortic specimens were determined. Differentially expressed lncRNA and mRNAs were then used to construct a competing endogenous RNA (ceRNA) network using Cytoscape software, and the five key lncRNA were identified. SNHG5 which was significantly downregulated in the AAA was chosen and analysis showed that it regulates mir‐205‐5p and SMAD4 by binding to mir‐205‐5p. Double luciferase reporter gene assays, RNA immunoprecipitation, and RNA knockdown studies were used to establish the relationship between SNHG5 and mir‐205‐5p. Apoptosis rate was determined using flow cytometry, whereas cell proliferation was evaluated using Edu, and 24 well Transwell assay. Western blot analysis was used to determine protein expression levels. Results The five differentially expressed lncRNAs were significantly correlated with 34 microRNAs and 112 mRNAs. mRNAs in the ceRNA network are implicated in protein binding, signal transduction, DNA and RNA transcription, development, and cell differentiation. SNHG5 was downregulated in the AAA and acts as a molecular sponge for mir‐205. Downregulation of SNHG5 induces expression of mir‐205‐5p. Increased mir‐205‐5p expression level inhibits SMAD4 production, thus inhibiting proliferation and migration and promotes apoptosis of smooth muscle cells. Conclusion Bioinformatics were used to explore molecular mechanism of AAA progression. The findings of this study show that lncRNA SNHG5 regulates proliferation and apoptosis of VSMC cells through modulation of the mir‐205‐5p/SMAD4 axis. Therefore, SNHG5 is a potential therapeutic target for AAA disease.